Sweet Syndrome With Painless Skin Lesions and Myopericarditis: A Case Report and Literature Review - Fakhruddin Almuzghi; Islam Elzouki; Moaz O. Moursi; Asiya Aqeel Thakur; Mahir Petkar (Clinical Case Reports)
ABSTRACT Sweet syndrome is a rare inflammatory disease that typically presents with painful erythematous skin lesions and fever. Although the skin lesions are generally painful on clinical examination, in this case, they were noted to be painless without tenderness. Moreover, our case is unique in that this patient had myopericarditis, a rare extracutaneous manifestation of sweet syndrome.